Impact of Digital Transformation Strategies on Organizational Performance in the Retail Industry in Cameroon - Pierre, Joseph (International Journal of Strategic Management, 2023)
Purpose: The aim of the study was to investigate the impact of digital transformation strategies on organizational performance in the retail industry in Cameroon. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The findings suggest that the implementation of digital transformation strategies in the retail industry in Cameroon has positively impacted organizational performance. Retailers adopting digital technologies have experienced improved customer engagement, streamlined operations, enhanced inventory management, and increased sales, ultimately leading to greater profitability and competitiveness in the market. Unique Contribution to Theory, Practice and Policy: The Resource-Based View (RBV) Theory, Innovation Diffusion Theory and Dynamic Capabilities Theory may be used to anchor future studies on the impact of digital transformation strategies on organizational performance in the retail industry in Cameroon. Retailers should explore partnerships, industry associations, and knowledge-sharing platforms to collectively address digital challenges, share best practices, and drive innovation. Regulatory bodies can encourage the responsible use of customer data for personalization while safeguarding privacy, thus fostering a conducive environment for digital transformation in the retail sector.